A Correlation Study Between Students’ Grammar Mastery and Writing Ability in The Second Semester Students of The English Education Study Program - Mesah, Murni Yunita; Tamelan, Thersia Magdalena; Ludji, Ifoni (Journal of Language, Education, Literature, and Culture, 2024)
Writing requires learners to articulate their thoughts and ideas in a coherent and organized manner. Understanding grammar can help students organize their thoughts in sentences that readers can easily understand. This study, title " A Correlation Study Between Students' Grammar Mastery and Writing Ability in The Second Semester Students of The English Education Study Program", aim to investigate the correlation between students' grammar mastery and their writing ability and to know the extent of the two variables correlate. The research method used is a quantitative method that applies a correlational study. The research instrument is documentary data, with the sample of this study being 19 students. The results show that there is a correlation between the two variables. The correlation between the two variables is proven by the rxy=0.747. The correlation coefficient is in the range of 0.60 to 0.80 showing a strong correlation, which indicates the extent of the correlation between the two variables. In simple terms, the null hypothesis (H0) was rejected. Meanwhile, the alternative hypothesis (H1) was accepted, which means that second-semester students of the English Study Program who are good at grammar are also likely to be good at writing.